1997
DOI: 10.1097/00000539-199710000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Vasomotor Effect of Thyroid Hormones on Rat Skeletal Muscle Resistance Arteries

Abstract: Thyroid hormones may have modest direct vasodilatory effects. This may partially account for the cardiovascular actions of the hormones in hyperthyroidism or when administered pharmacologically in cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
3
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 26 publications
7
32
3
3
Order By: Relevance
“…Our preliminary experiment showed that T 3 was devoid of effects in preparations in which the Ach-induced relaxation was less than 50%; therefore, we applied the protocol of T 3 administration only to C57BL/6 mice. In agreement with the results previously reported in rat skeletal muscle resistance arteries [7], T 3 is effective in our present work at all concentrations used (10 -9 to 10 -7 M ). This result indicates that the mesenteric arteries are a target site for T 3 , where it regulates physiological vascular tone.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our preliminary experiment showed that T 3 was devoid of effects in preparations in which the Ach-induced relaxation was less than 50%; therefore, we applied the protocol of T 3 administration only to C57BL/6 mice. In agreement with the results previously reported in rat skeletal muscle resistance arteries [7], T 3 is effective in our present work at all concentrations used (10 -9 to 10 -7 M ). This result indicates that the mesenteric arteries are a target site for T 3 , where it regulates physiological vascular tone.…”
Section: Discussionsupporting
confidence: 94%
“…The disruption of TRα in this background significantly blunted the mesenteric response to Ach. This result contrasts with that obtained in the tail artery of TRα-mutant mice [4], but is in agreement with the fact that TH has been shown to stimulate NO production via both endothelium-dependent [7] and endothelium-independent mechanisms [30]. In addition, the responses to SNP, AII and PE were also all blunted in TRα 0/0 C57 mice.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…For years, studies have suggested that T3 causes vascular relaxation exclusively via EC. However, compelling data support a rapid vasorelaxant effect of T3 also occurring via VSMC [11, 33]. Therefore, identification of vasodilatory mechanisms activated independently of endothelium by T3 is imperative.…”
Section: Discussionmentioning
confidence: 99%